Adsorbent materials obtained from palm waste and its potential use for contaminants removal from aqueous solutions (2019)
This work reports the production of an adsorbent material obtained by H3PO4 chemical activation of oil palm waste (fiber). The experiments were carried out to explore methylene blue uptake by this adsorbent. The influence of initial dye concentration and adsorbent dosage was investigated. The adsorption equilibrium data of methylene blue onto the adsorbent material were best fitted to the Langmuir model. The maximum adsorption capacity monolayer was of 20.85 mg g-1, which showed to be high compared to other adsorbent materials reported in the literature. Adsorption of methylene blue onto adsorbent material followed pseudo-second order model. The structural and chemical characterization of the adsorbent material was carried out by using various analytical techniques. FTIR showed the formation of oxygenated functional groups on the surface, which are very important for adsorption applications because they act as active sites capable of interacting with dye molecules. © 2019 Published under licence by IOP Publishing Ltd.